Pizarnik through Levine’s Looking Glass: How Subversive Is the Scribe? - Stratford, Madeleine (TTR, 2006)
AbstractSuzanne Jill Levine is known above all for her English translations of Cabrera Infante, Sarduy and Puig, with whom she worked closely. While a lot has been written about her translations of fiction by men, little research has been done on her translations of women writers. In this paper, I analyse a selection of her English renditions of Alejandra Pizarnik in order to see how Levine behaves when translating the poetic work of a woman. First, considering that Levine describes herself as a “subversive scribe, ‘transcreating’ writing that stretches the boundaries of patriarchal discourse,” how does the fact that she shares the author’s gender affect her “transcreations?” Then, bearing in mind that Levine has often stressed the complexity of fiction translation, refuting the “common belief that novels are easier to translate than poetry,” how does she deal with the translation of lyrical poems? And last, how rebellious is she when translating an author who has passed away and whom she cannot consult?